Quantum Tomography of Rydberg Atom Graphs by Configurable Ancillas - Kangheun Kim; Jaewook Ahn (PRX Quantum, 2023)
Tomographic reconstruction of the many-body quantum state of a scalable qubit system is of paramount importance in quantum computing technologies. However, conventional approaches that use tomographically orthogonal base measurements require precise and individual qubit controls, which are often experimentally daunting. Here we propose, as a quantum mechanically robust alternative, using configurable ancillas, the continuously tunable interactions of which can generate independent base measurements tomographically sufficient for the quantum state reconstruction of the system of interest. Experimental tests are performed for Rydberg atom arrays in N-body W states, the results of which demonstrate reliable high-fidelity full quantum state reconstruction by the proposed method.